EVALUATION OF THE APRICOT GENE POOL IN THE SOUTHERN URALS - S. I. Tukach; Z. K. Klimenko (Труды по прикладной ботанике, генетике и селекции)
Anatomic, morphological and physiological characteristics of the genus Zinnia L. have been studied in the climatic environments of the foothill zone of the Crimea. Xeromorphic features have been identified in the anatomical structure of the stem and leaf in the species Zinnia рeruviana L., Z. violacea Cav., and Z. haageana Regel. Comparative analysis of the genus Zinnia L. has shown that its species differ in the degree of lignification of their tissues and the intensity of pubescence. As for water scarcity, the most drought-resistant species has been found: Z. violacea Cav. (4.6%).